Parasitic infections of Piaractus mesopotamicus and hybrid (P. mesopotamicus x Piaractus brachypomus) cultured in Brazil - Franceschini, Lidiane; Zago, Aline Cristina; Schalch, Sergio Henrique Canello; Garcia, Fabiana; Romera, Daiane Mompean; Silva, Reinaldo Jose Da (Colégio Brasileiro de Parasitologia Veterinária, 2013)
Este estudo avaliou a ocorrência de infecções parasitárias em pacus Piaractus mesopotamicus e do híbrido patinga (P. mesopotamicus x P. brachypomus) procedentes da região Noroeste do Estado de São Paulo, Brasil. Peixes de três pisciculturas foram avaliados bimestralmente: A - Reprodução e Larvicultura (n = 16 pacus / n = 19 patingas), B-Engorda n = 35 patingas), e C- Pesque-pague (n = 28 pacus / n = 7 patingas). Trinta e cinco peixes de cada propriedade foram coletados de fevereiro de 2010 a fevereiro de 2011, para análises parasitológicas. Os parasitas encontrados foram: Mymarothecium viatorum, Anacanthorus penilabiatus, Notozothecium janauachensis (Dactylogyridae, Monogenea), Trichodina spp., Ichthyophthirius multifiliis, Chilodonella sp. (Protozoa), Myxobolus spp., Henneguya spp. (Myxozoa), Rondonia rondoni, Contracaecum sp. (Nematoda), and Dolops carvalhoi (Crustacea). Dentre os peixes analisados, 62,9% de “A” e 100% de “B” e “C” estavam infectados/infestados por pelo menos uma espécie de parasita. Pacus (n = 44) apresentaram maior suscetibilidade a infestações por Anacanthorus penilabiatus, e patingas (n = 61), por Mymarothecium viatorum (p < 0.05). A profilaxia e cuidados durante o manejo (alimentação, transporte e estocagem), associados ao monitoramento da qualidade de água reduzem o estresse o qual os peixes cultivados estão submetidos, sendo medidas imprescindíveis para o controle de patógenos.

This study evaluated the occurrence of parasitic infections in the “pacu” fish Piaractus mesopotamicus and the “patinga” hybrid (P. mesopotamicus x Piaractus brachypomus) in the northwest of São Paulo State, Brazil. Fish from the following three fish farms were evaluated every two months: A, a hatchery and larviculture farm (n = 16 pacu / n = 19 patinga), B, a growout farm (n = 35 patinga) and C, a fee-fishing property (n = 28 pacu / n = 7 patinga). Thirty-five fish from each property were collected from February 2010 to February 2011 and subjected to parasitological analysis. The parasites found were the following: Mymarothecium viatorum, Anacanthorus penilabiatus, Notozothecium janauachensis (Dactylogyridae, Monogenea), Trichodina spp., Ichthyophthirius multifiliis, Chilodonella sp. (Protozoa), Myxobolus spp., Henneguya spp. (Myxozoa), Rondonia rondoni, Contracaecum sp. (Nematoda), and Dolops carvalhoi (Crustacea). Of the fish examined, 62.9% from “A” and 100% from “B” and “C” were infested with at least one parasite species. Pacu fish (n = 44) showed a higher susceptibility to Anacanthorus penilabiatus infestations, whereas patinga (n = 61) were more susceptible to Mymarothecium viatorum (p < 0.05). Appropriate fish handling (nutrition, transport and storage), in conjunction with monitoring of water quality, can reduce the stress to which the farmed fish are exposed and is essential for pathogen control.
Infecções parasitárias de Piaractus mesopotamicus e do híbrido (P. mesopotamicus x Piaractus brachypomus) cultivados no Brasil
Keywords: Manejo; helmintos; protozoarios; controle de estocagem; qualidade de agua; Handling; helminths; protozoans; storage control; water quality